Some Fixed-Point Results for a -Weak Contraction in -Metric Spaces - Wasfi Shatanawi; Mihai Postolache (Abstract and Applied Analysis)
We introduce the concepts of a -weak contraction mapping of types and and we establish some fixed point theorems for a -weak contraction mapping of types and in complete -metric spaces. Our results generalize several well-known comparable results in the literature.